EGFR-Mutated Squamous Cell Lung Cancer and Its Association With Outcomes - Jin, Rui; Peng, Ling; Shou, Jiawei; Wang, Jin; Jin, Yin; Liang, Fei; Zhao, Jing; Wu, Mengmeng; Li, Qin; Zhang, Bin; Wu, Xiaoying; Lan, Fen; et al. (Frontiers in Oncology, 2021)
Background: The therapeutic efficacy of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in advanced EGFR-mutant lung squamous cell carcinoma (SCC) patients remains uncertain. Furthermore, the factors underlying the responsiveness have not been fully investigated. We therefore investigated the link between genomic profiles and EGFR-TKI efficacy. Material and Methods: We consecutively enrolled stage IV, EGFR-mutant-, and EGFR-TKI-treated patients with SCC. Patients with EGFR wild-type lung SCC and EGFR-mutant lung adenocarcinoma were consecutively enrolled as controls, and next-generation sequencing (NGS) was performed. Results: In total, 28 EGFR-mutant lung SCC, 41 EGFR-mutant lung adenocarcinoma, and 40 EGFR wild-type lung SCC patients were included. Among the patients with EGFR mutations, shorter progression-free survival (PFS) was observed in SCC compared to adenocarcinoma (4.6 vs. 11.0 months, P<0.001). Comparison of the genomic profiles revealed that EGFR-mutant SCC patients had similar mutation characteristics to EGFR-mutant adenocarcinoma patients, but differed from those with EGFR wild-type SCC. Further exploration of EGFR-mutant SCC revealed that mutations in CREBBP (P=0.005), ZNF217 (P=0.016), and the Wnt (P=0.027) pathway were negatively associated with PFS. Mutations in GRM8 (P=0.025) were associated with improved PFS. Conclusions: EGFR-mutant lung SCC has a worse prognosis than EGFR-mutant adenocarcinoma. Mutations in other genes, such as CREBBP, ZNF217, GRM8 or Wnt that had implications on PFS raise the possibility of understanding mechanisms of resistance to EGFR-TKI in lung SCC, which will aid identification of potential beneficial subgroups of patients with EGFR-mutant SCCs receiving EGFR-TKIs.